2019
DOI: 10.1007/978-3-030-06115-9
|View full text |Cite
|
Sign up to set email alerts
|

Surface Modification of Nanoparticles for Targeted Drug Delivery

Abstract: the material is concerned, specifically the rights of translation, reprinting, reuse of illustrations, recitation, broadcasting, reproduction on microfilms or in any other physical way, and transmission or information storage and retrieval, electronic adaptation, computer software, or by similar or dissimilar methodology now known or hereafter developed. The use of general descriptive names, registered names, trademarks, service marks, etc. in this publication does not imply, even in the absence of a specific … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…A 4-azido-2,3,5,6-tetrafluorobenzyl methacrylate (ABMA) homopolymer was recently modified with phosphines after polymerization to give stable iminophosphoranes and prepare well-defined spherical, worm-shaped, vesicular NP gels with azide-functional cores that underwent a thermally reversible degelation [118,119]. Multicomponent modification of NPs with phenylacetaldehyde, morpholine, piperidine, or the N,N -dimethylethylene cross-linker led to the corresponding amidine derivatives (core modification) in one step.…”
Section: Photo-reactivementioning
confidence: 99%
“…A 4-azido-2,3,5,6-tetrafluorobenzyl methacrylate (ABMA) homopolymer was recently modified with phosphines after polymerization to give stable iminophosphoranes and prepare well-defined spherical, worm-shaped, vesicular NP gels with azide-functional cores that underwent a thermally reversible degelation [118,119]. Multicomponent modification of NPs with phenylacetaldehyde, morpholine, piperidine, or the N,N -dimethylethylene cross-linker led to the corresponding amidine derivatives (core modification) in one step.…”
Section: Photo-reactivementioning
confidence: 99%
“…These challenges will be overcome with more knowledge of pharmacokinetics. To demonstrate the fabricated surface modified lipid-based nanocarriers’ safe and effective clinical application, the toxicity problems with them must also be looked into …”
Section: Current Challenges and Future Perspectivesmentioning
confidence: 99%
“…4−6 Polymeric nanoparticles have been proposed as one promising modality for brain drug delivery due to their advantages, including enhanced solubility of drug payload, reduced drug metabolism, biodegradability, enhanced therapeutic efficacy, and reduced toxicity relative to the administration of free drugs. 7,8 Additionally, polymeric nanoparticles can be easily engineered by tuning their physicochemical properties based on the targeted application with enhanced delivery to brain. 7−11 Nevertheless, these studies are still far from optimal as the accumulation in the liver reduces the overall availability of the drug in the CNS.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Polymeric nanoparticles have been proposed as one promising modality for brain drug delivery due to their advantages, including enhanced solubility of drug payload, reduced drug metabolism, biodegradability, enhanced therapeutic efficacy, and reduced toxicity relative to the administration of free drugs. , Additionally, polymeric nanoparticles can be easily engineered by tuning their physicochemical properties based on the targeted application with enhanced delivery to brain. Nevertheless, these studies are still far from optimal as the accumulation in the liver reduces the overall availability of the drug in the CNS. , One of the common ways to enhance drug delivery across the BBB is to adorn the surface of these bespoke nanomaterials with targeting ligands that can be recognized by the receptors expressed on the BBB and internalized via the process of endocytosis. , In addition to the nanoparticle size, shape, surface charge, ligand type, conjugation strategy, orientation, and ligand density have recently emerged as critical parameters that significantly dictate the mechanism and kinetics of its cellular interaction. , In a recent review article, it was demonstrated that when the ligand density increases, the cellular association increases to a limit, after which a constant or decreased association is observed . Interestingly, targeted nanoparticles often qualitatively report the ligand density as ‘low’, ‘intermediate’, and ‘high’, or as a percentage and only a few reports quantitatively determine the number of ligands per nanoparticles.…”
Section: Introductionmentioning
confidence: 99%